Upconversion properties of SrF2:Yb3+, Er3+ single crystals. Issue 12 (25th February 2020) - Saleta Reig, D.; Grauel, B.; Konyushkin, V. A.; Nakladov, A. N.; Fedorov, P. P.; Busko, D.; Howard, I. A.; Richards, B. S.; Resch-Genger, U.; Kuznetsov, S. V.; Turshatov, A.; Würth, C.
Abstract : We present the excitation power and doping concentration dependent upconversion properties of SrF2 :Yb 3+, Er 3+ single crystals. The determined optical properties of this bulk material can serve as benchmark values for cubic-phase nanomaterials. Abstract : Synthesis of new upconversion (UC) materials that can convert near-infrared excitation light into visible emission light with high efficiency has crucial importance for energy and bio-applications. Herein, SrF2 single crystals with a doping concentration of 2 mol% Er 3+ and 2–8 mol% Yb 3+ were synthesized and the optical properties were studied. The absorption cross-section of the different doping ions was calculated. To identify the most efficient and brightest material absolute excitation power dependent UC photoluminescence quantum yields ( ϕ UC ) and brightness values were determined. In addition, excitation characteristics and luminescence lifetimes were analysed to understand the changes in population pathways and possible quenching mechanisms. A dominant two-photon population behaviour of the red and green emission bands was observed for all investigated doping concentrations of Yb 3+ and Er 3+ . The ϕ UC value of 6.5% measured using 230 W cm −2 of 976 nm excitation for SrF2 crystal co-doped with 2 mol% Er 3+ and 3 mol% Yb 3+ . These findings broaden the scope of efficient UC materials apart from the record UC material β-NaYF4 :Yb 3+, Er 3+ and provide benchmark values for cubic-phase and especially SrF2 - nano and micrometer sized materials.